Kekuasaan Jawa: Pandangan Elit Kraton Surakarta dan Yogyakarta - Isbodroini Suyanto-Gunawan (Antropologi Indonesia, 2005)
During the Javanese historical development since the First Mataram Empire until today, Javanese cultural concepts as cultural syncretism of early Hindu-Buddhism, latter Hindu-Buddhism and Islam tends to be preserved. In its contact with later concepts from the west, such as formal education, modern politics and the entrance of various ideologies such as nationalism, capitalism, socialism, democracy and so on, has not negated those Javanese cultures. The main problem posed in this article is as follow: to what extent Javanese value of political power has been embraced by elites from Surakarta and Yogyakarta palaces. Whether their values are still strong or has it been diminished. Results reached in this research are: (1) Dominant perception of the elite, shows that their understanding of Javanese political power is still strong. They still strongly embraced the palace tradition and fully involved in all palace's rituals; (2) Western cultural penetration has not able to negate the strong rooted Javanese culture from these palace's elites. Their spirits are still bound to the Javanese culture which surrounded their palace; (3) Javanese sense of political power will play important role when it is positioned as spiritual power to those "njawani" rulers. Key words: Javanese culture; power; political elite; cultural traditions.